Society, representation and textuality: the critical interface - Bhattacharjee,Sukalpa; Thomas,C.Joshua (ed.) (New Delhi, 2013)
Society, Representations and Textuality: The Critical Interface brings together papers from various critical perspectives of Humanities and Social Sciences. The work takes stock of the recent developments in critical theory and cultural studies, studies the impact of these developments on the understanding of social reality and the human predicament in India and brings together scholars from North East India who are engaged in the project of understanding society and communities in their chosen intellectual practice. The book is the first-ever attempt to establish a dialogic encounter between critical practices in Humanities and Social sciences, hitherto considered to be autonomous in their own disciplinary boundaries. Further, the volume addresses issues of identity and autonomy of a multicultural India, particularly with reference to the interface between hegemonic cultures and politically and culturally persistent smaller communities. A significant feature of this book is its attempt to theorize and describe the myriad manifestations of the critical interface between society and literary or cultural productions.
Keywords: Culture